Understanding immigrant entrepreneurship: A home-country entrepreneurial ecosystem perspective - Carson Duan; Kamaljeet Sandhu; Bernice Adei Kotey (New England Journal of Entrepreneurship (NEJE), 2021)
Purpose Given the importance of immigration and immigrant entrepreneurs in advanced economies, the authors take an entrepreneurial ecosystem perspective to study the home-country benefits possessed by immigrant entrepreneurs and how home-country entrepreneurial ecosystem factors affect immigrant entrepreneurial motivations, activities and outcomes. Design/methodology/approach This conceptual research paper follows McGaghie, Bordage and Shea's (2001) four-step new theory creation process, which suggests that new theories can be created through facts extraction from the extant literature. Findings The authors propose that although immigrant entrepreneurs are unable to take full benefit of the host-country entrepreneurial ecosystem due to blocked mobility, they do have capabilities to access and use their home-country entrepreneurial resources and opportunities. The authors further propose that home-country entrepreneurial capital can be systemically analyzed through the framework of the entrepreneurial ecosystem. The results imply that immigrant entrepreneurship as a social and economic phenomenon can be studied more holistically from both host- and home-country perspectives compared to the traditional research boundary of the host-country only. Research limitations/implications The research focuses on the identification of home-country effects on immigrant entrepreneurship through the lens of the entrepreneurial ecosystem. Testable propositions provide directions for future empirical research on the field of immigrant entrepreneurship from a home-country perspective. The research concludes that a holistic immigrant entrepreneurship study should consider dual (host- and home-country) entrepreneurial ecosystems. Practical implications Immigrant entrepreneurs benefit from both host- and home-country entrepreneurial ecosystems. This paper suggests co-effects of dual entrepreneurial ecosystems lead to a high rate of entrepreneurship and business success within some immigrant groups. Policymakers can increase economic activities by developing and deploying programs to encourage immigrants to embed in host- and home-country entrepreneurial ecosystems. Originality/value Based on the framework of the entrepreneurial ecosystem, this paper brings a novel perspective to examining home-country effects on immigrant entrepreneurship. It theoretically conceptualizes that immigrants have higher entrepreneurship rates than native-born populations because they have access to extra home-country entrepreneurial capital.
Keywords: 650; Entrepreneurial ecosystem; Immigrant business; Immigrant entrepreneurship; Transactional entrepreneur; Venture creation business determinant